MOTIVASI KERJA KARYAWAN PADA LEMBAGA PENYIARAN PUBLIK TELEVISI REPUBLIK INDONESIA SULAWESI TENGAH - Oliyda, Ririn (Katalogis, 2018)
As a public broadcasting, TVRI Central Sulawesi required to provide a competitive broadcast with private television. On the contrary, it could not able to provide broadcast quality better, because as a matter of fact, the official employees had not able to provide quality employment appropriate expected yet due to lack of work motivation. The problem of this research was how the official employees work motivation of Public Broadcasting TVRI Central Sulawesi. This research analyzed descriptively and qualitatively. The informants were three leaders and three staff of TVRI Central Sulawesi by using purposive sampling technique. Technique of taking and collecting data consisted of observation, interview and documentation. Abraham H Maslow theory was also used in order to know the official employee work motivation. The result figured the official employees work motivation was quite good on two aspects, namely the convenience of threats work and social needs aspects. While the aspect of maintaining the viability, self-esteem and self-actualization needs were less perceived by the official employees. In addition, salaries or fees earned was not sufficient to maintain the viability of them, no reward or recognition for work performance achieved by them and the lack of support for self the official employee in education and vocational training.